Exploring the Influence of EWOM on Purchase Intention: The Mediating Roles of Trust, Value CO-Creation, and Brand Image in Apple Product - Grady Deven; Sihombing, Sabrina O. (Universitas Pelita Harapan, 2024)
The rise of digital communication has transformed traditional word of mouth (WoM) into electronic Word of Mouth (eWOM), significantly influencing consumer behavior. This study investigates the impact of eWOM on purchase intention, with a focus on Apple products among Indonesian students. The research explores the mediating roles of trust beliefs, value co-creation, hedonic brand image, and functional brand image in this relationship. Utilizing a quantitative approach, data were collected from 240 respondents through an online questionnaire, and the results were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings demonstrate that eWOM has a positive effect on purchase intention, with trust beliefs and value co-creation acting as significant mediators. Moreover, both hedonic and functional brand image were found to positively mediate the relationship between eWOM and purchase intention. These results highlight the importance of eWOM as a strategic tool in influencing consumer decisions, especially for premium brands like Apple. The study provides insights for marketers on leveraging trust, value creation, and brand image to enhance purchase intention through eWOM.